Full-duplex mac protocol based on csma/ca for switching transmission mode - Kim, Jin Ki; Lee, Won Jae; Kim, Jae Hyun (Electronics (Switzerland), 2021)
Full-duplex (FD) radios can transmit and receive packets simultaneously in the same frequency band. Although this potentially doubles the spectral efficiency, it also causes inter-node interference, which was not an issue for half-duplex (HD) radios and can significantly reduce FD radio throughput. This paper proposes a hybrid transmission switching algorithm to reduce performance degradation due to inter-node interference. In contrast to previous studies that only considered channel capacity, we determine the transmission mode by considering the modulation and coding scheme (MCS). The access point compares the required transmission time for HD, FD, and hybrid mode and selects the mode with the best network throughput. We also designed an analytical model to evaluate network throughput for the proposed algorithm. In particular, we consider FD pair probability, which has not been addressed previously. Analytical and simulation results verify that the proposed algorithm improves network performance.
Keywords: FD pair probability; Hybrid transmission; MCS region; WLAN